PENGARUH PENERAPAN TEKNIK PETA PIKIRAN (MIND MAPPING) TERHADAP KEPERCAYAAN DIRI SISWA DALAM PELAJARAN PAI DI SMP IT AL-RIDWAN KARAWANG - Aminarti, Putri Andina; Darmiyanti, Astuti; Hakim, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted to examine the effect of implementing the Mind Mapping technique on students’ self-confidence in Islamic Religious Education (PAI) learning at SMP IT Al-Ridwan Karawang. The research employed a quantitative approach using a survey method. The sample consisted of 35 eighth-grade students of SMP IT Al-Ridwan Karawang. Data were collected through questionnaires to assess the implementation of the Mind Mapping technique and observation sheets to measure students’ self-confidence. Data analysis included validity testing, reliability testing, normality testing, linearity testing, simple linear regression analysis, t-test analysis, and coefficient of determination (R²) analysis. The findings revealed that the mean score of the Mind Mapping variable was 63.40, while the mean score of students’ self-confidence was 66.34, both of which were categorized as moderate. The results of the simple linear regression analysis produced the regression equation Y = 11,153 + 0.870 X, indicating a positive relationship between the implementation of the Mind Mapping technique and students’ self-confidence. Furthermore, the hypothesis test showed a t-value of 15.767 with a significance level of 0.000 (< 0.05), indicating that the proposed hypothesis was accepted. The coefficient of determination (R²) was found to be 88.3%, demonstrating that the Mind Mapping technique contributed substantially to enhancing students’ self-confidence. Therefore, it can be concluded that the implementation of the Mind Mapping technique has a positive and significant effect on students’ self-confidence in learning Islamic Religious Education at SMP IT Al-Ridwan Karawang.